Nutrition Deficiencies in Children With Intestinal Failure Receiving Chronic Parenteral Nutrition. Issue 2 (13th December 2017) - Namjoshi, Shweta S.; Muradian, Sarah; Bechtold, Hannah; Reyen, Laurie; Venick, Robert S.; Marcus, Elizabeth A.; Vargas, Jorge H.; Wozniak, Laura J.
Abstract: Background : Home parenteral nutrition (PN) is a lifesaving therapy for children with intestinal failure (IF). Our aims were to describe the prevalence of micronutrient deficiencies (vitamin D, zinc, copper, iron, selenium) in a diverse population of children with IF receiving PN and to identify and characterize risk factors associated with micronutrient deficiencies, including hematologic abnormalities. Methods : Data were collected on 60 eligible patients through retrospective chart review between May 2012 and February 2015. Descriptive statistics included frequencies, medians, interquartile ranges (IQRs), and odds ratios (ORs). Statistical analyses included χ 2, Fisher's exact, t tests, and logistic, univariate, and multivariate regressions. Results : Patients were primarily young (median age, 3.3 years; IQR, 0.7–8.4), Latino (62%), and male (56%), with short bowel syndrome (70%). Of 60 study patients, 88% had ≥1 deficiency and 90% were anemic for age. Of 51 patients who had all 5 markers checked, 59% had multiple deficiencies (defined as ≥3). Multivariate analysis shows multiple deficiencies were associated with nonwhite race (OR, 9.4; P = .012) and higher body mass index z score (OR, 2.2; P = .016). Children with severe anemia (hemoglobin <8.5 g/dL) made up 50% of the cohort. Nonwhite race (OR, 6.6; P = .037) and zinc deficiency (OR, 11; P = .003) were multivariate predictors of severe anemia. Conclusions : Micronutrient deficiency and anemia are overwhelmingly prevalent in children with IF using chronic PN. This emphasizes the importance of universal surveillance and supplementation to potentially improve quality of life and developmental outcomes. Future research should investigate how racial disparities might contribute to nutrition outcomes for children using chronic PN.